Consistent within‐individual plasticity is sufficient to explain temperature responses in red deer reproductive traits. (15th September 2019) - Froy, Hannah; Martin, Julien; Stopher, Katie V.; Morris, Alison; Morris, Sean; Clutton‐Brock, Tim H.; Pemberton, Josephine M.; Kruuk, Loeske E. B.
Abstract: Warming global temperatures are affecting a range of aspects of wild populations, but the exact mechanisms driving associations between temperature and phenotypic traits may be difficult to identify. Here, we use a 36‐year data set on a wild population of red deer to investigate the causes of associations between temperature and two important components of female reproduction: timing of breeding and offspring size. By separating within‐ versus between‐individual associations with temperature for each trait, we show that within‐individual phenotypic plasticity (changes within a female's lifetime) was entirely sufficient to generate the observed population‐level association with temperature at key times of year. However, despite apparently adequate statistical power, we found no evidence of any variation between females in their responses (i.e. no "IxE" interactions). Our results suggest that female deer show plasticity in reproductive traits in response to temperatures in the year leading up to calving and that this response is consistent across individuals, implying no potential for either selection or heritability of plasticity. We estimate that the plastic response to rising temperatures explained 24% of the observed advance in mean calving date over the study period. We highlight the need for comparable analyses of other systems to determine the contribution of within‐individual plasticity to population‐level responses to climate change. Abstract : Female red deer on the Isle of Rum, Scotland show plasticity in reproductive traits in response to temperature variation in the year leading up to calving. Phenotypic plasticity was sufficient to generate the observed population‐level associations for both calving date and calf birth weight, and there was no evidence for variation in plasticity among individuals.